Modulatory effect of filarial infection on the systemic hormone levels in subjects with metabolic syndrome (DM-LF5) - Sibi, Joy Manohar; Mohan, Viswanathan; Deepa, Mohan; Babu, Subash; Aravindhan, Vivekanandhan (Frontiers in Endocrinology, 2022)
Metabolic syndrome (MS) refers to a group of co-morbidities which include central obesity, hypertension, hyperglycemia and dyslipidemia. Previously, we reported that childhood lymphatic filariasis (LF) confers significant protection against type-1 and type-2 forms of diabetes, by means of immunomodulation. In the present study, we studied the effect of LF on endocrine dysfunction in MS and Non-MS Patients in baseline and after 10 years of follow-up. We quantified the serum levels of pancreatic hormones (insulin and glucagon), incretins (Ghrelin, GIP and GLP-1) and adipokines (leptin, adiponectin, adipsin, visfatin, PAI-1 and resistin) by multiplex bead array system. MS (both LF- and LF+) subjects had increased insulin levels compared to NMS (both LF- and LF+) subjects. MS-LF+ subjects had significantly increased levels of glucagon, ghrelin, GIP and GLP-1 and decreased levels of adipsin, compared to MS-LF- subjects. Interestingly this effect was short-lived and was not seen in the follow-up samples. Overall, LF infection might confer limited short-term beneficial effects against MS, by means of modulating the incretin levels, either directly or indirectly.